A Diagnostic Scoring System for Sacroiliac Joint Pain Originating from the Posterior Ligament. Issue 2 (10th June 2016) - Kurosawa, Daisuke; Murakami, Eiichi; Ozawa, Hiroshi; Koga, Hiroaki; Isu, Toyohiko; Chiba, Yasuhiro; Abe, Eiji; Unoki, Eiki; Musha, Yoshiro; Ito, Keisuke; Katoh, Shinsuke; Yamaguchi, Takuhiro
Abstract : Objective. Sacroiliac joint (SIJ) pain originating from the posterior ligament manifests in not only the buttocks but also the groin and lower extremities and thus may be difficult to discern from pain secondary to other lumbar disorders. We aimed to develop a simple clinical diagnostic tool to help physicians distinguish between patients with SIJ pain originating from the posterior ligament and those with lumbar disc herniation (LDH) or lumbar spinal canal stenosis (LSS). Design. Prospective case-control study. Patients and Methods. We evaluated 62 patients with SIJ pain originating from the posterior ligament and 59 patients with LDH and LSS. Pain areas, pain increasing positions, provocation test, and tenderness points were investigated. A scoring system based on multivariate logistic regression equations using the investigated items was developed. Results. Two pain areas (the posterosuperior iliac spine (PSIS) detected by the one-finger test and groin), pain while sitting on a chair, provocation test, and two tenderness points (PSIS and the sacrotuberous ligament) had high odds ratios (range, 25.87–1.40) and were used as factors in the scoring system. An integer score derived from the regression coefficient and clinical experience was assigned to each identified risk factor. The sum of the risk score for each patient ranged from 0–9. This scoring system had a sensitivity of 90.3% and a specificity of 86.4% for a positivity cutoff point of 4. Conclusion. The scoring system can help distinguish between patients with SIJ pain originating from the posterior ligament and those with LDH and LSS.